Inpatient Psychiatric Care for Children and Adolescents: Increasing the Integration of Service and Science. Issue 4 (2nd October 2022) - Patriquin, Michelle; Thompson, Alysha D.; Walker Lowry, Kelly; Leffler, Jarrod M.; Reynolds, Elizabeth K.
ABSTRACT: The past decade has seen a significant increase in rates of mental illness for youth, including a dramatic increase in rates of suicide. This rise in youth mental illness coincides with a growing utilization of inpatient psychiatric care for children and adolescents. Now, more than ever, evidence-based interventions – and the science to develop these treatments – is needed for youth inpatient psychiatric care. Herein, we outline the strengths, weaknesses, opportunities, and threats (SWOT) for increasing the science in youth inpatient psychiatric settings to develop new evidence-based services.